1999
DOI: 10.1128/aem.65.4.1652-1657.1999
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Genes Encoding Nitrite Reductase in Denitrifying Bacteria

Abstract: Using consensus regions in gene sequences encoding the two forms of nitrite reductase (Nir), a key enzyme in the denitrification pathway, we designed two sets of PCR primers to amplifycd 1- and Cu-nir. The primers were evaluated by screening defined denitrifying strains, denitrifying isolates from wastewater treatment plants, and extracts from activated sludge. Sequence relationships ofnir genes were also established. Thecd 1 primers were designed to amplify a 778 to 799-bp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(136 citation statements)
references
References 35 publications
3
131
0
2
Order By: Relevance
“…The copper-type nitrite reductase has been found in various denitrifying bacteria, nitrifying bacteria [12], and archaea [30]. Most nirK genes have been described in three subdivisions (K, L, and Q) of the Proteobacteria [7,9,10,12]. For the most part, the phylogeny of NirK sequences in this study correlated with the phylogeny of 16S rRNA genes.…”
Section: Genetic Diversity Of Cu-type Nitrite Reductasesupporting
confidence: 66%
“…The copper-type nitrite reductase has been found in various denitrifying bacteria, nitrifying bacteria [12], and archaea [30]. Most nirK genes have been described in three subdivisions (K, L, and Q) of the Proteobacteria [7,9,10,12]. For the most part, the phylogeny of NirK sequences in this study correlated with the phylogeny of 16S rRNA genes.…”
Section: Genetic Diversity Of Cu-type Nitrite Reductasesupporting
confidence: 66%
“…Because denitrification is catalyzed by a diverse group of bacteria, archaea, and fungi (Zumft 1997), research on the abundance and diversity of denitrifiers in the environment has focused on the functional genes involved in the denitrification pathway. Although some studies have utilized the periplasmic and membranebound NO 3 À reductase genes (napA and narG) (Flanagan et al 1999, Gregory et al 2000, Mergel et al 2001) and a gene encoding nitrous oxide reductase (nosZ; Michotey et al 2000, Scala and Kerkhof 2000, Mergel et al 2001, Rich et al 2003, most molecular investigations of bacterial denitrification in natural environments (see review by Bothe et al 2000) have utilized nitrite reductase (nirS and nirK; Linne von Berg and Bothe 1992, Hallin and Lindgren 1999, Braker et al 2000, Michotey et al 2000, Mergel et al 2001, because it catalyses the first committed step that leads to a gaseous intermediate. The reduction of nitrite is catalyzed by either one of two entirely different enzymes in terms of structure and the prosthetic metal, the cytochrome cd1 (encoded by the gene nirS) and the copper-containing nitrite reductases (encoded by the gene nirK).…”
Section: Molecular Approachesmentioning
confidence: 99%
“…The multiple alignments of the nucleotide sequences for both copper and cytochrome cd-type nitrite reductase (nirK and nirS respectively) genes, including those recently deposited in public databases demonstrated that the previously constructed primers contained residues that were mismatched to recently identified sequences such as F1aCu, R3Cu (Hallin and Lindgren, 1999), 583F (Yan et al, 2003), nirK5R (Braker et al, 1998;Santoro et al, 2006) Heme 832F and Heme 1606R (Liu et al, 2003) for nirK genes, and Cd3aF (Michotey et al, 2000), F1aCu, R3Cd (Hallin and Lindgren, 1999;Throbäck et al, 2004), nirS1F, nirS6R (Braker et al, 1998), Copper 583F and Copper 909R (Liu et al, 2003) for nirS genes. However, it was difficult to design and establish novel primer sequences covering all of the nirK or nirS sequences present.…”
Section: Detection and Quantification Of Dissimilatory Nitrite Reductmentioning
confidence: 99%